2016
DOI: 10.21760/jaims.v1i2.3673
|View full text |Cite
|
Sign up to set email alerts
|

Dose schedule of Rasa Aushadhis

Abstract: Rasashastra deals with the Rasa Aushadhis, the drugs of metallic and mineral origin. Mercury is used in most of the Rasaaushadhis. The toxicity of Mineral and metallic preparations are reduced to such an extent by various procedures of Shodhana, Marana etc. that Mercury converts its inherent property of toxicity into medicinal property. Rasa Aushadhis works quickly on the body because due to their small particle size, their absorption starts from the oral mucosa itself. The action of drugs depends largely upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…But when studies were conducted on it, the drug was found not to be nephrotoxic but protective to the kidneys from nephrotoxins. [29] . Modern medicines are proving insufficient for curing disease, many of them provide only symptomatic relief or acts as a placebo and also causing deleterious effects on the body on long time consumption.…”
Section: Applications Of Kpr and Ptr In Practicementioning
confidence: 99%
“…But when studies were conducted on it, the drug was found not to be nephrotoxic but protective to the kidneys from nephrotoxins. [29] . Modern medicines are proving insufficient for curing disease, many of them provide only symptomatic relief or acts as a placebo and also causing deleterious effects on the body on long time consumption.…”
Section: Applications Of Kpr and Ptr In Practicementioning
confidence: 99%
“…Rasa Aushadhis work in smaller doses and are faster in action, therefore, they are required in smaller doses20,21 . Rasa Aushadhis get absorbed quickly into the body.…”
mentioning
confidence: 99%